Complete Visual Recovery From Severe Outer Retinitis After Tonsillitis. Issue 4 (11th December 2021) - Kawashima, Rumi; Matsushita, Kenji; Hashida, Noriyasu; Kuniyoshi, Kazuki; Fujikado, Takashi; Nishida, Kohji
Abstract : Background: To report a case of severe acute bilateral outer retinitis after tonsillitis and rapid morphologic and functional recovery after steroid treatment. Methods: Observational case report. Results: A 26-year-old woman with acute bilateral blurred vision that developed after tonsillitis underwent spectral-domain optical coherence tomography (SD-OCT) that showed photoreceptor outer segment damage. Full-field electroretinography (ERG) and multifocal ERG were nonrecordable. The patient had a remarkable anatomic and functional recovery in response to steroid treatment; however, partial damage remained around the macula on SD-OCT, and an adaptive optics imaging system showed damaged cone photoreceptors. Conclusions: Prednisolone is an effective treatment for a disease that is believed to be due to suspicious involvement of the autoimmune system. Even severe outer retinitis can recover completely with rapid diagnosis and treatment.